2014
DOI: 10.1007/s00464-014-3944-5
|View full text |Cite
|
Sign up to set email alerts
|

Foramen of Winslow hernia: a minimally invasive approach

Abstract: Hernias through the foramen of Winslow comprise 8 % of all internal hernias and the majority contain incarcerated bowel. Clinical signs are often non-specific and delay in diagnosis associated with a mortality rate that approaches 50 %. Management is urgent surgical reduction with bowel decompression and resection of devitalized bowel. A foramen of Winslow hernia (FWH) has traditionally been managed via an exploratory laparotomy incision and the vast majority of cases describe an open approach. We describe a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 19 publications
(25 reference statements)
0
69
0
4
Order By: Relevance
“…This is likely to be due to the early assessment and diagnosis, resulting in more stable patients, who are suitable for a minimally invasive operation in contrast to exploratory laparotomy. Widespread access to laparoscopic equipment, as well as widely disseminated laparoscopic training also plays an important role [5,6]. There has been some discussion as to whether to perform prophylactic surgical measures to prevent recurrence (foramen closure), with insufficient data to support either [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be due to the early assessment and diagnosis, resulting in more stable patients, who are suitable for a minimally invasive operation in contrast to exploratory laparotomy. Widespread access to laparoscopic equipment, as well as widely disseminated laparoscopic training also plays an important role [5,6]. There has been some discussion as to whether to perform prophylactic surgical measures to prevent recurrence (foramen closure), with insufficient data to support either [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…One case was excluded, due to the lack of detailed patient history and presentation. The cases were published between 1967 and 2016 describing 24 patients with internal hernias through the foramen of Winslow, 1–3 5–21…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of this diagnosis may be obtained intraoperatively. Our review showed that erect chest and/or abdominal X-rays were done in many of the reported cases to help rule out a bowel perforation 5 7 12–15 17 19–22. Obstructive series and abdominal ultrasound were also used.…”
Section: Discussionmentioning
confidence: 99%
“…Management involves urgent surgical reduction with bowel decompression and resection of nonviable tissue, frequently open surgery will be required. 7,8 Historically, patients presenting with typical abdominal pain were investigated with explorative laparotomy, the diagnosis was made intraoperatively and often led to bowel resection because of ischemia. Such diagnostic delay therefore resulted in high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%